Scholastic performance of freshmen in the University of the Philippines College of Agriculture during the academic year 1960-1961 - Ables, Higino A.; Castillo, Gelia Tagumpay; Saguiguit, Gil F.
The students included in the study were among the first to take the College Freshman Examination in the University of the Philippines. One part of the examination was the scholastic aptitude test, which included a quantitative and linguistic test. The achievement test was the other part, covering English, Mathematics, Pilipino, Social Science, and Natural sciences.
Keywords: University of the Philippines (Los Banos). College of Agriculture -- Students; College freshmen -- Rating of -- Philippines -- Los Banos (Laguna).; Academic achievement -- Philippines -- Los Banos (Laguna).